Current-Mode Square-Rooting Circuit Based on CMOS Translinear - Wongprommoon, Natapong; Thongdit, Preecha; Prommee, Pipat (My University, 2018)
In this paper, a new current-mode square-rooting circuit based on translinear principle is proposed. The saturation mode of MOS transistors is used for realizing the proposed circuit with ± 1.5V power supplies. Square-rooting circuit is realized from the translinear type-A and current computation which uses totally eighteen MOS transistors. The circuit has two inputs which one performs as input and another one for a variable gain. Two input positions are similar characteristic which are able to swap generally. The gain of proposed square-rooting can be electronically tuned by bias current. The current output is accurately compared with the ideal square-rooting function. The error at current output is achieved lower than 4%along 150μA of input range. High frequency sinusoidal signal can be operated up to 5MHz. The proposed circuit is suitable for applying in the varieties of analogue signal-processing applications. The simulation results are depicted to confirm the theoretical analysis by using PSpice. Moreover, layout and post layout simulation results are included.
Keywords: CMOS; Current-mode; Square-rooting; Translinear